Bertrem the aesthetic - Crook, Jeff.; Berberick, Nancy Varian; Grubber, John.; Herbert, Mary H.; Kauth, Dennis; Weis, Margaret (Renton, Wash. : Wizards of the Coast ; [Kustannuspaikka tuntematon] : Distributed in the U.S. by Holtzbrinck Publising, 2001)
Includes map of The city of Qualinost.
Includes poems by Genin Crystáltus from "Heroes and children: the diary and poetry of an angry rebel" by Jeff Crook.
"Bertrem, member of the Aesthetic Order and heir to the great Astinus, master chronicler of Krynn, has once again sent forth his agents to gather information about the lives of the ordinary people of Ansalon"--Prelim. page.
At head of title: Dragonlance.
"Maps by Dennis Kauth"--Verso t.p.
Keywords: Fantasy fiction; Fantasy fiction, American; Dragons in literature; Krynn (Imaginary place); Fantasy fiction